KEANEKARAGAMAN JENIS KUPU-KUPU DI DESA BOMBA KECAMATAN LORE SELATAN KABUPATEN POSO - Toding, Gideon; Rosyid, Abdul; Sustri, Sustri; Toknok, Bau; Rukmi, Rukmi; Ihsan, Moh (Jurnal Belantara, 2024)
The Sintuwu Maroso KPH area, which is located in Bomba Village, South Lore District, has quite high biodiversity, one of which is butterflies. Butterflies are insects that belong to the order Lepidoptera. Butterflies play an important role in the ecosystem and maintain balance and enrich natural biodiversity. These insects are also important in agriculture, art, culture and human civilization. The Sintuwu Maroso KPH area, Bomba Village, South Lore District, Poso Regency, is a primary forest with maintained sustainability. Primary forest is a good place for butterfly habitat, so it is necessary to protect these butterflies. And research on these butterflies in the Sintuwu Maroso KPH area is still rare, as butterflies play an important role in plant pollination. Therefore, it is necessary to research the diversity of butterfly types.  This research was carried out for 2 (two) months from October 2023 to November 2023, which took place in the KPH Sintuwu Maroso area, Bomba Village, South Lore District, Poso Regency, Central Sulawesi. Data collection and the number of individual types of butterflies used the Point Count method with eleven points. Data analysis used in the research is: species diversity index, species richness index, and species evenness index.